The Effect of Non-Performing Loans (NPL) and Capital Adequacy Ratio (CAR) on Profitability (ROA) at PT. Bank Central Asia (BCA), TBK - Rita Anggriani; Puji Muniarty Muniarty (Ilomata International Journal of Management, 2020)
The purpose of this research is to find out and analyze whether there is an influence between Non Performing Loans and Capital Adequacy Ratio both partially and simultaneously on the Profitability (ROA) of PT. Bank Central Asia, Tbk. The approach taken in this research is associative and quantitative. The population of this study was all subjects at PT. Bank Central Asia (BCA), Tbk for 44 years, namely 1974-2018 with a total sample of 9 years, namely 2010-2018. The sampling method is a purposive sampling method. While the data analysis technique uses classical assumptions, multiple linear regression, hypothesis testing (t-test and F test) and the coefficient of determination. The results of this study prove that Non-performing Loans do not affect the Return On Assets. However, Capital Adequacy Ratio has a significant effect on Return On Asset. While simultaneously this study proves that Non-Performing Loans and Capital Adequacy Ratio affect the Return On Assets at PT. Bank Central Asia, Tbk.